31 A pragmatic pilot study of ankle mobilizations and exercise in canadian armed forces members with lateral ankle sprain. (12th October 2015) - Robitaille, E; Agur, A; Hébert, LJ; Switzer-McIntyre, S
Abstract : Background: Limited ankle dorsiflexion may cause difficulty with walking, running and increase lateral ankle sprain (LAS) recurrence risk in Canadian Armed Forces (CAF) members. Manual ankle mobilizations are commonly applied by physiotherapists to CAF members with LAS to restore ankle dorsiflexion however, research into their effectiveness as an adjunct treatment is limited. Objectives: To investigate the effectiveness of adding manual ankle mobilizations to a comprehensive rehabilitation program to improve ankle dorsiflexion in CAF members with acute LAS. Design: Pragmatic randomised pilot study. Setting: CAF health services centre. Participants: Twenty CAF members with LAS <7 days old without contraindications to manual ankle mobilizations entered and nineteen completed the study. Interventions: All participants completed a standardised comprehensive rehabilitation program. Ten were randomised to an experimental group who also received 6 sessions of manual ankle mobilizations, while the other ten also received 6 sessions of sham mobilizations. Main outcome measurements: At baseline, 2, and 12 weeks a physiotherapist blinded to group allocation administered the Bent Knee Dorsi Flexion Test and recorded the scores of the; Visual Analogue Scale, Lower Extremity Functional Scale, Foot and Ankle Disability Index, the number of days until return to work and number of recurrences. Results: There were no significant differences in mean ankle mobility between the experimental (95.2 ± 47.5 mm) and sham groups (94.7 ± 36.9 mm) at 2 weeks (p > 0.05). There was a significant interaction between ankle dorsiflexion and time (p < 0.001) but not between groups (p = 0.460). However, the mean differences within both groups between baseline and 2 weeks exceeded the minimal clinically important differences reported for ankle dorsiflexion, pain and function. Conclusions: These results suggest that for the first 2 weeks following acute LAS CAF physiotherapists should emphasise participation in a comprehensive rehabilitation program and then evaluate the need for manual ankle mobilizations.